Effectiveness of Ointment Therapy Products Based on Snakehead Fish Extract (Channa Striata) Combined with Black Honey (Epis Dorsata) on Post-Operative Wound Patients - Mulidan Mulidan; Muhammad Andry (GLOBAL HEALTH SCIENCE GROUP, 2024)
Snakehead fish (Channa striata) is a type of freshwater fish that is widely known by the public. The efficacy and benefits of this fish, especially in increasing albumin which is important for the body, have been scientifically proven. Snakehead fish has a very high protein content and is a source of albumin for patients with hypoalbuminemia and wounds. Black honey is also known to have great benefits in the process of tissue formation in wounds. The purpose of this study was to evaluate the effectiveness of therapeutic ointments based on snakehead fish extract combined with black honey in post-operative patients. Methods: This study used a quasi-experimental method with a post-test only with control group design, a sampling technique with purposive sampling with inclusion criteria involving 30 participants who were divided into control and intervention groups. The intervention group was given snakehead fish extract ointment and black honey for 2 weeks. Observations of the wounds were carried out before and after the application of the ointment in both groups. Pre and post intervention scores were measured using the REEDA (Redness, Edema, Ecchymosis, Discharge, Approximation) instrument, with a score range of 0-2 for good wounds and 9-15 for bad wounds. Statistical analysis used the Paired T-test with a significance level of p<0.005. Results: The results showed that patients who received the intervention experienced an increase in wound healing scores. In the intervention group, 7 respondents (56.7%) showed good wound healing and 8 respondents (53.3%) showed moderate healing. Concentration F1 was proven to be more effective than F2 and F3. Based on statistical tests, there was a significant difference between the intervention and control groups, with the Paired Sample Test showing a p value <0.000 in the intervention group, while the control group was not significant (p>0.334) with an average intervention value (12.86) and control (11.53). Conclusion: Ointment based on snakehead fish extract combined with black honey has been proven to be effective in accelerating wound healing in postoperative patients.